The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adom.202202867
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐Bias Long‐Wave Infrared Nanoantenna‐Mediated Graphene Photodetector for Polarimetric and Spectroscopic Sensing

Abstract: Graphene has attracted great interest for integrated photonic platforms in the long‐wave infrared (LWIR) for spectroscopic and polarimetric sensing due to the capability of on‐chip integration, fast response, and broadband operation. However, graphene suffers from low photoresponsivity and thus poor sensing performance due to weak absorption. Polarization detection using graphene is hindered by its small in‐plane anisotropy. Here, nanoantenna‐mediated graphene photodetectors (NMGPDs) are proposed to enhance re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…The phenomenon of infinite PR values is similar to the recently reported nanoantennamediated semimetal photodetectors where the PR values can cover a wide range (1→∞/-∞→−1) by tuning the antennas orientation. [24,54,55] To further confirm the polarization-induced reverse in polarized photocurrent, the time-dependent dynamic photoresponse by varying the polarization angles at V G of -12 V and V DS of 0 V is shown in Figure 5h and Figure S21 (Supporting Information). It is clearly observed that the photocurrent varies with angles and has a sign reversal from positive to negative.…”
Section: Reverse In Photocurrent By Light Polarizationmentioning
confidence: 94%
“…The phenomenon of infinite PR values is similar to the recently reported nanoantennamediated semimetal photodetectors where the PR values can cover a wide range (1→∞/-∞→−1) by tuning the antennas orientation. [24,54,55] To further confirm the polarization-induced reverse in polarized photocurrent, the time-dependent dynamic photoresponse by varying the polarization angles at V G of -12 V and V DS of 0 V is shown in Figure 5h and Figure S21 (Supporting Information). It is clearly observed that the photocurrent varies with angles and has a sign reversal from positive to negative.…”
Section: Reverse In Photocurrent By Light Polarizationmentioning
confidence: 94%
“…In addition, as the symmetry of the optical antennas increases, the anisotropy of the photovoltage weakens, consolidating that the BPVE is caused by the asymmetry of the optical antennas. Following this success, most recently, Xie et al have constructed a self-driven long-wave infrared photodetector by modifying double L-shaped Au nanoantennas onto a graphene channel [258]. Impressively, the hybrid device manifests distinct polarized-resolved photovoltage and demonstrates a sensitive noise-equivalent polarization-angle perturbation down to 0.05 • .…”
Section: Integration Of Low-symmetry Optical Antennasmentioning
confidence: 99%
“…Graphene's high electrical conductivity enhances the performance of IoT communication systems, enabling faster and more reliable data transmission. A graphene-based nano-antenna is a tiny antenna structure made from graphene [ 48 ] which can operate across a wide range of frequencies, including terahertz [ 49 , 50 ], due to graphene's tunable conductivity. At the nanoscale, their size facilitates precise signal control and manipulation of light and electromagnetic waves, while graphene's high electrical conductivity minimizes signal losses and maximizes efficient radiation, culminating in enhanced signal reception and transmission.…”
Section: Graphene Iot-based Applicationsmentioning
confidence: 99%